Genetic variation in Otos is associated with cisplatin-induced ototoxicity. (October 2014) - Spracklen, Timothy F; Whitehorn, Heather; Vorster, Anna Alvera; Ramma, Lebogang; Dalvie, Sameera; Ramesar, Rajkumar S
Background : Ototoxicity is an adverse drug reaction that may limit the effective use of cisplatin chemotherapy. Given the reported in vitro protective role of the gene Otos in response to cisplatin, this study aimed to explore the potential of Otos as a genetic modifier of ototoxicity.Patients & methods : One hundred South African cisplatin-receiving cancer patients with baseline and follow-up audiometric data were screened for variation in exonic target regions of Otos using direct cycle sequencing.Results : A total of 29 genetic variants were identified. The G alleles of Otos rs77124181 (c.-192-182C>G) and rs2291767 (c.-192-22A>G) were over-represented in ototoxicity-free patients (p = 0.022). Cumulative cisplatin dose and anatomical site of cancer were also associated with ototoxicity, while self-reported ethnicity associated with the ototoxic severity.Conclusion : This study indicates a potentially protective role for the variant G alleles of SNPs rs77124181 and rs2291767 in Otos against the development of cisplatin-induced ototoxicity. Original submitted 4 April 2014; Revision submitted 15 July 2014